Association of body mass index with risk of early-onset colorectal cancer: systematic review and meta-analysis - Li, Hengjing; Boakye, Daniel; Chen, Xuechen; Hoffmeister, Michael; Brenner, Hermann (The American journal of gastroenterology, 2021)
INTRODUCTION: Incidence of colorectal cancer (CRC) in young adults has been increasing in recent decades in many countries for still widely unclear reasons. Suspected candidates include increasing prevalence of overweight and obesity, but specific evidence on their role for early-onset CRC (EOCRC) is sparse. We conducted a systematic review and meta-analysis to summarize available evidence on the association of body mass index (BMI) with EOCRC. METHODS: We systematically searched PubMed, EMBASE, and Web of Science up to February 2021 for studies that evaluated the association of BMI (before diagnosis but not near diagnosis) with CRC risk and reported specific results for EOCRC. Results from studies with similar BMI groupings were summarized in meta-analyses using random-effects models. RESULTS: Twelve studies were eligible and included. Results of 6 studies were pooled in meta-analyses, which yielded a higher risk of EOCRC for overweight and obesity (BMI ≥25 kg/m2) compared with normal weight (odds ratio [OR] 1.42, 95% confidence interval [CI] 1.19-1.68). An increasing risk with increasing BMI was observed, with much higher risk for obesity (OR 1.88, 95% CI 1.40-2.54) than for overweight (OR 1.32, 95% CI 1.19-1.47). DISCUSSION: Obesity is a strong risk factor for EOCRC, and its increasing prevalence in younger generations is likely to substantially contribute to the increase in EOCRC. Efforts to limit the obesity epidemic in adolescents and younger adults may be crucial for reducing CRC incidence in future generations of adults.
Gesehen am 06.12.2021